Luminescent silver nanoclusters decorated on ZnO tetrapods: a detailed understanding of their role in photoluminescence features - Rodrigues, Joana (2022)
Optical spectroscopic measurements are conducted on luminescent silver nanocluster (AgNC) decorated ZnO tetrapods (ZnO Tp), AgNC@ZnO Tp, synthesized via a colloidal route. Their properties are compared with those of the corresponding AgNC and ZnO Tp to understand their impact on the photoluminescence (PL). Raman spectroscopy reveals the high structural integrity of the ZnO structure in the AgNC@ZnO Tp. PL analysis of the ZnO Tp shows a well-resolved near band edge emission and a green band comprised by the overlapping of at least three emitting optical centres. The addition of AgNC to ZnO Tp in the hybrid material enhances the emission from ZnO surface states. The recombination of the AgNC in water solution is dominated by a red emission band peaking at ∼1.9 eV and the PL excitation spectra monitored at the band maximum reveal that the red PL of AgNC is preferentially populated by well-defined excitation bands corresponding to discrete electronic transitions of the NCs. Yet, a shift to lower energies of the AgNC emission occurs in the AgNC@ZnO Tp hybrid when excited with energies below the ZnO bandgap, while for energies above this value no emission from the AgNC was observed, with the ZnO-related recombination dominating the spectra. A gradual loss in the PL intensity of the AgNC is observed in the hybrid with increasing time, which is consistent with their coalescence to transform into larger Ag nanoparticles (NPs) on the tetrapod surface, as revealed by confocal microscopy.